“The Orchestra, in its Sounds, Defies Virtue…”: The Role of the Erotic in the Works of Massenet. - Annegret Fauser (Transposition)
Massenet’s opera Esclarmonde, premiered in Paris during the 1889 Exposition Universelle, offers a particularly powerful case study for the ways in which a libretto articulating socially conservative structures meshes with, and enables, musically progressive expressivity. This essay analyses the opera from a perspective of feminist critique, centering on the title role and providing a close reading of both libretto and score as they play with the erotic and the exotic. The analysis is framed through the lens of the opera’s reception in 1889 by way of socio-political readings and of discussions of music’s aesthetic capacity for sensual immediacy.